(untitled) (REGE Revista de Gestão, 2017)
Academia has been analyzing organic certification labels for at least 10 years, with emphasis on their importance and level of knowledge. However, little has been written about the associations and meanings they have for consumers. This article aims to study this meaning through a quantitative research, survey type, with 388 respondents. The data were analyzed through a cluster analysis which revealed the existence of three customer groups, according to the meaning assigned to the labels. The three segments were called “Greeners”, “GMO-Freers” and “Don’t Carers”. The first group, the “Greeners”, is the largest (46.6%), and brings greater association with the meanings “sustainable agriculture” and “environmentally friendly” and is associated with older people. The second, the “GMO-Freers”, presents closer association with the meaning “It does not make use of genetically modified/transgenic seeds” and is related to people who have already done post-graduation courses (24.7% of respondents). Finally, the third, “Don’t Carers”, (28.7%), shows lower association to the label’s meanings in general, and is also more concentrated in an elite group of consumers. The research comes to the conclusion that the label’s meanings may change according to different consumer profiles. On theoretical grounds the present study fills a gap in the literature in a way that it deepens a first analysis of the label’s meaning, by reaching a second level of consumer attributions, and revealing the need for understanding this meaning among different groups. Based on the consumer behavior model presented by Kotler and Keller (2012), it is possible to show how consumers’ psychological aspects can be influenced by social characteristics in the way the groups perceive organic labels. The practical contributions to manufacturers and certifying agencies of organic products are also discussed